2012
DOI: 10.3109/09273972.2012.655838
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Divergence in Children With Intermittent Exotropia

Abstract: Purpose To report fusional divergence in children with intermittent exotropia (XT). Methods We retrospectively studied 32 children with intermittent XT (aged 4 to 13 years) and 38 visually normal non-strabismic children. Fusional divergence break points were measured using a prism bar, starting from a naturally fused state. Distribution of divergence break points was evaluated. Subnormal fusional divergence was defined as below the 5th percentile in visually normal children. In children with intermittent XT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
5
10
1
Order By: Relevance
“…Another study in Chinese children showed similar results [ 17 ]. There was no significant correlation between divergence amplitude detected by prism bar and control score, which is similar to the findings by Liebermann et al ( r = −0.29, P = 0.11) [ 10 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another study in Chinese children showed similar results [ 17 ]. There was no significant correlation between divergence amplitude detected by prism bar and control score, which is similar to the findings by Liebermann et al ( r = −0.29, P = 0.11) [ 10 ].…”
Section: Discussionsupporting
confidence: 90%
“…Sharma et al reported reduced divergence amplitudes in IXT subjects that differed from the results of our present study [ 11 ]. Liebermann et al have reported that most children with IXT have normal near fusional divergence, but that nearly half had reduced distance fusional divergence [ 10 ]. They found that the distribution of fusional divergence break points in IXT was normal at near but bimodal at distance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adult subjects were included in the study, and fusion data were collected after the angle of deviation had been corrected using prisms. Furthermore, Liebermann et al (2012) believe that common measurement methods may not reveal the true divergence amplitudes. Most IXT patients have normal fusional divergence at near fixation, and approximately half show decreased fusional divergence at distance fixation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculate that fusional divergence may indicate how robust fusion is and have prognostic significance. 80…”
Section: Strabismusmentioning
confidence: 99%